UNFOLDING TOMORROW - Vaishnav, Jaimine (TEDx Talks, 2025)
Dr. Jaimine Vaishnav is an educator and TEDxGateway speaker known for his work on street entrepreneurship and mindset development. With 14 years of academic experience, he combines research, storytelling, and mindfulness practices to help individuals understand business, society, and the human mind in a deeper way. Educator and TEDxGateway speaker Dr. Jaimine Vaishnav is an educator and TEDxGateway speaker known for his work on street entrepreneurship and mindset development. With 14 years of academic experience, he combines research, storytelling, and mindfulness practices to help individuals understand business, society, and the human mind in a deeper way. This talk was given at a TEDx event using the TED conference format but independently organized by a local community.
: TEDxPWSSama Youth
Please click on the link to view the video on the YouTube.